Nanosized Cs-pollucite zeolite synthesized under mild condition and its catalytic behavior - Mohammad, Aleid Ghadah S.; Ahmad, Nur Hidayahni; Goldyn, Kamila; Mintova, Svetlana; Ling, Tau Chuan; Ng, Eng Poh (IOP Publishing, 2018)
Nanoscale cesium-pollucite zeolite (ANA topology) free of organic template is synthesized free of organic template. The crystallization is taken place at mild temperature and pressure (180 °C, 22 bar) compared to previous works. Powder XRD analysis reveals that the nanocrystals can be crystallized from a clear precursor solution of 16.5SiO2:1Al2O3:5.3Cs2O:175H2O within 50 h. The resulting nanocrystals exhibit trapezohedron shape and has a Si/Al ratio of 4.11. The nanocrystals possess a mean particle size of 79.4 nm and they are colloidally stable in water. In addition, Perkin condensation of benzaldehyde with acetic anhydride catalyzed by nanosized Cs-pollucite zeolite under non-microwave instant heating condition is also demonstrated and discussed.